(3MhGTi Ydi QSGdI GdRhQGA GdeQOGfis - (3LdGd GdOjf eMeO Hf CSYO GdUOjbi GdOhGfis; (3GdOhGfj , eMeO Hf GSYO GdUOjbj, LdGd GdOjf,J (B918 (3g` s
(3ChdgG (B:s
(3CeG HYO GdMeO dhdjI hGdUdGI Ydi fHjg aEfi deG YQaJ ai JgPjH GdQSGdI GdehSheI HGdRhQGA GdeTJedI Ydi RjO ef GdMbGFb hfHP ai GdObGFb hgj ef NUGFU GdReGf Cf CcJH YdjgG MhGTi s
(3BNQgG (B:s
( (3ChdFc cGdCfYGe Hd ge GVd(B) (3GYGP HGddg hSGFQ GdeSdejf ef GdVdGd hGdRdd hhabfG deG gh jYajfG efg GdYbO hGdbhd hGdYed hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B47s
Keywords: (3GdadSaI hGdefWbs